(untitled) (Praxis Educativa, 2013)
This paper presents the results of a literature review that considers documents and research work on environmental education (EA) in general, and on EA and legislation in particular, produced at the international, regional and national levels, and guided by the questions: What do works linking EA and education in Argentine legislation contend? In what context, within the EA field, are they inserted? Through the referred reviews we characterize the EA international and Latin American panorama, and analyze the contributions of five articles and a book relevant to our focus on Argentina. Without claiming to have done thorough research, this approach allowed us to perceive the need to deepen the studies that, apart from describing the content of the various laws, analyze its meaning in the historical context in which each regulation was passed, as well as the relationship between forces in the field of environmental education.